Dispersion State and Damage of Carbon Nanotubes and Carbon Nanofibers by Ultrasonic Dispersion: A Review - Harald Rennhofer; Benjamin Zanghellini (Nanomaterials, 2021)
Dispersion of carbon nanotubes and carbon nanofibers is a crucial processing step in the production of polymer-based nanocomposites and poses a great challenge due to the tendency of these nanofillers to agglomerate. Besides the well-established three-roll mill, the ultrasonic dispersion process is one of the most often used methods. It is fast, easy to implement, and obtains considerably good results. Nevertheless, damage to the nanofibers due to cavitation may lead to shortening and changes in the surface of the nanofillers. The proper application of the sonicator to limit damage and at the same time enable high dispersion quality needs dedicated knowledge of the damage mechanisms and characterization methods for monitoring nano-particles during and after sonication. This study gives an overview of these methods and indicates parameters to be considered in this respect. Sonication energy rather than sonication time is a key factor to control shortening. It seems likely that lower powers that are induced by a broader tip or plate sonicators at a longer running time would allow for proper dispersions, while minimizing damage.